THE ROLE OF PREPOSITIONS IN TEXT FORMATION - Abdulhakimova Sarvinoz Parda kizi; Ahmadaliyeva Khosiyatposhsha (Лучшие интеллектуальные исследования, 2023)
Annotation: In this article, preposition-nominal complexes, which perform the function of denotation and can be used in an independent preposition before the text, are fully described about the role of prepositions in text formation.